Profitability and Valuation Ratios as Predictors of Stock Prices: Contemporary Evidence from Indonesia’s Capital Market - Gunawan, Hendri; Elshinta, Ria (Indonesian Financial Review, 2025)
This study examines the impact of profitability and valuation ratios, as measured by Net Profit Margin (NPM) and Price-to-Book Value (PBV), on the stock prices of companies listed on the Indonesia Stock Exchange (IDX). Motivated by inconsistent findings in prior research, this study employs purposive sampling based on 12 annual observations and applies multiple linear regression, along with classical assumption tests. Results show that NPM positively and significantly affects stock prices, while PBV has a positive but statistically insignificant effect at the 5% level. The adjusted R² of 0.730 indicates that 73% of stock price variation is explained by the two variables, with 27% influenced by other factors. Findings confirm the role of profitability as a strong predictor of stock prices in Indonesia’s capital market and provide practical implications for investors and corporate managers in improving firm market value.